2005
DOI: 10.1128/jvi.79.18.11677-11684.2005
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of CCR5-Δ32 Heterozygosity and the CCR5 Promoter Polymorphism −2459 A/G on CCR5 Expression and Resistance to Human Immunodeficiency Virus Type 1 Transmission

Abstract: Exposed seronegative individuals (ES) with persistent high-risk sexual behavior may be less susceptible to human immunodeficiency virus type 1 (HIV-1) infection because they carry the chemokine receptor (CR) gene alleles CCR5 open reading frame (ORF) ⌬32, CCR5 promoter ؊2459G, or CCR2 ORF 64I (CCR2-64I), all of which have been found to diminish HIV-1 infectivity and/or disease progression. To investigate this, we determined the haplotypes for these three genetic loci in 93 ES and 247 low-risk control individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 64 publications
(90 reference statements)
6
62
1
Order By: Relevance
“…In contrast, measured CD4 density values were similar among the donors (range of 22.4-27.0 ϫ 10 3 CD4 receptors/cell) (data not shown). These density values for CCR5 and CD4 are within the ranges reported by others (9)(10)(11)(12). Interestingly, VCV EC 50 values varied ϳ 20-fold among the different donors and correlated positively with CCR5 densities (Spearman's correlation test; r ϭ 0.746, P ϭ 0.0034).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…In contrast, measured CD4 density values were similar among the donors (range of 22.4-27.0 ϫ 10 3 CD4 receptors/cell) (data not shown). These density values for CCR5 and CD4 are within the ranges reported by others (9)(10)(11)(12). Interestingly, VCV EC 50 values varied ϳ 20-fold among the different donors and correlated positively with CCR5 densities (Spearman's correlation test; r ϭ 0.746, P ϭ 0.0034).…”
Section: Resultssupporting
confidence: 64%
“…We first evaluated the effect of CCR5 levels on the antiviral activity of VCV using cell lines JC10 (ϳ 2 ϫ 10 3 CCR5/cell) and JC57 (ϳ 9 ϫ 10 3 CCR5/cell), which express CD4 levels similar to those in normal CD4 T cells and whose CCR5 densities correspond to the approximate lower and upper levels of CCR5 expression in donors (9)(10)(11)(12). We infected each clone with the R5 HIV-1 strains JRFL and CC1/85 (multiplicity of infection, MOI ϭ 0.01) in the presence of varying concentrations of VCV (0.03-30 nM) for 3 h. For comparison, cells also were infected in the presence of the reverse transcriptase inhibitor efavirenz (0.003-3 nM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that a 59029-G/A polymorphism in the CCR5 promoter was associated with a differential regulation of CCR5 transcription (26). Other studies demonstrated that some individuals who practice high-risk sexual behavior may resist infection because they posses one CCR5⌬32 allele plus a 59029-A/G genotype combination, which is apparently associated with relatively weak CCR5 expression (18). This newfound complexity in the vagaries of CCR5⌬32 expression and function might increase the clarity of the genomic analysis of risk factors for HIV infection and disease progression.…”
Section: Ccr5mentioning
confidence: 99%
“…However, our recent study suggests that individuals with the combination of heterozygous CCR5-32 and P1 CCR5 promoter genotype (see below) are relatively resistant to HIV-1 transmission [74]. According to most reports [47-49, 55, 75-81] but not all [82,83], individuals with heterozygous CCR5-32 progress from HIV-1 infection to AIDS more slowly than persons with two normal CCR5 alleles.…”
Section: Introductionmentioning
confidence: 94%